A new species of Aphonopelma (Araneae: Mygalomorphae: Theraphosidae) from the Madrean pine-oak woodlands of northeastern Sonora, Mexico - Hendrixson, Brent E. (Zootaxa, 2019)
The tarantula spider genus Aphonopelma Pocock, 1901 has received considerable attention in recent years but the group’s diversity remains poorly understood in Mexico, particularly in the pine-oak woodlands of the Sierra Madre Occidental and associated Madrean “Sky Islands”. A pair of tarantulas discovered from an unsampled region in the Sierra de Bacadéhuachi (the westernmost range of the Sierra Madre Occidental) in northeastern Sonora was found to be closely related to four species from the Madrean “Sky Islands” in Arizona and New Mexico. An integrative approach for delimiting species (incorporating data from molecular phylogenetics, morphology, distributions, and breeding periods) suggests that the specimens from Sierra de Bacadéhuachi belong to an undescribed species that is herein named Aphonopelma bacadehuachi sp. nov. This new species adds to our knowledge of an increasingly diverse assemblage of Aphonopelma from the Madrean Pine-Oak Woodlands Hotspot. Collaborations between Mexican and American researchers are needed to accelerate discovery and description of the group’s remaining diversity, particularly in light of the many threats facing the ecoregion including habitat degradation and climate change.